Assessing occupational hazards and safety: a study of healthcare workers’ knowledge, attitudes, and practices in Iraq - Sevinç, Nergiz; Murad, Zainab; Nacar, Erkay; Arıcan, Ali Ayberk (Scientific Reports in Medicine, 2025)
Objective: Occupational health and safety are vital in reducing morbidity and mortality from workplace hazards. This study examines healthcare workers’ knowledge, attitudes, and practices regarding occupational risks to support targeted interventions and policy development.Methods: A cross-sectional descriptive study was conducted at Baqubah General Hospital, Diyala Province, Iraq, between 11/20/2023 and 02/20/2024. 400 permanent healthcare worker —including doctors, pharmacists, nurses, technicians, and support staff—were selected through simple random sampling. Data were collected via a structured, face-to-face questionnaire adapted from validated knowledge, attitudes, practices surveys. The questionnaire included 8 knowledge, 5 attitude and 8 practice items, each scored as ‘1’ for correct/positive and ‘0’ for incorrect/negative responses. Median scores were used for evaluation.Results: Most participants were aged 25–34(62%), with nearly equal gender distribution. About 38% had good knowledge of occupational hazards, higher among males (p=0.028), non-smokers (p=0.026), non-medication users (p=0.042). Only 32% exhibited a positive attitude toward safety, which was significantly associated with male gender (p=0.017) and medication use (p=0.034). Good safety practices were reported by 37%, higher in males (p=0.046), laboratory staff (p=0.006), and non-medication users (p=0.008). No significant associations with age, education or years of service.Conclusions: The study identified significant gaps in occupational hazard awareness: only one-third had good knowledge, nearly two-thirds had poor knowledge, and less than one-third showed a positive attitude toward occupational health and safety. Healthcare institutions should improve safety by ensuring continuous supply of personal protective equipment and mandatory, targeted training.